Association of 48 type 2 diabetes susceptibility loci with fasting plasma glucose and lipid levels in Chinese Hans. (May 2018) - Liu, Jia; Wang, Lu; Qian, Yun; Dai, Juncheng; Shen, Chong; Jin, Guangfu; Hu, Zhibin; Shen, Hongbing
Abstract: Aim: Dozens of susceptibility loci have been identified by type 2 diabetes (T2D) genome wide association study (GWAS) in Europeans. In our previous studies, we systematically evaluated the association of 48 susceptibility loci with T2D risk in Chinese Hans. Because dyslipidemia and hyperglycemia are implicated in the pathogenic process of T2D, we further evaluated whether these 48 single nucleotide polymorphisms (SNPs) were related to fasting plasma glucose (FPG) or lipid levels in Chinese Hans. Methods: The 48 SNPs were genotyped by using the Taqman OpenArray Genotyping System and iPLEX Sequenom MassARRAY platform. Multiple linear regression was used to assess the relationship between genetic variants and FPG and lipid levels among 3281 non-diabetic, healthy Chinese Hans. Results: After adjusting for age, gender, body mass index (BMI), smoking status and drinking status, the T allele of rs13266634 in the SLC30A8 gene was significantly associated with decreased glucose level (β = −0.0119, P = 8.05 × 10 −5 ), whereas the T allele of rs896854 in the TP53INP1 gene was associated with increased triglyceride (TG) level (β = 0.0342, P = 9.61 × 10 −4 ) and decreased high-density lipoprotein cholesterol (HDL-C) level (β = −0.015, P = 3.24 × 10 −3 ) after Bonferroni correction. We also conducted a meta-analysis consisted of 11 studies and confirmed that SNP rs896854 in the TP53INP1 gene was associated with T2D risk. Conclusion: Our findings indicated that SNP rs13266634 in SLC30A8 was associated with glucose level and SNP rs896854 in TP53INP1 was associated with lipid level.